Productivity and Chemical Parameters in the Bottom Soil of 1 and 3 years operated pond of Black Tiger Prawn Penaeus monodon Fab. Culture - Nirmala, Kukuh; Yuniar, E.; Budiardi, T. (Indonesian Society of Scientific Aquaculture (ISSA), 2005)
This study was carried out to observe the productivity and bottom soil chemical aspects of 1 year and 3 years operated pond of black tiger prawn Penaeus monodon Fab. culture. The results of study depicted that pond operated for 3 years contained higher (P